The Rise of the Urban Piety Movement: Jamaah Maiyah as an Urban Spiritualism and Emerging Religiosity in the Public Sphere - Alam, Lukis; Lahmi, Ahmad; Alam, Meredian; Aminah, Aminah (Jurnal Ilmiah Peuradeun, 2022)
Recently, an intense discussion has developed among religion and social issues researchers on the discourse of spiritualism. The existence of spiritualism has changed parts of human civilization, including religious attitudes and expressions that exist in the public sphere. Therefore, in this study, the authors examined the discourse of spiritualism exemplified by Jamaah Maiyah Cak Nun. The model of spiritualism that the authors adopted was different in context from the cultural spiritualism studied by many scientists. This study sought to elaborate and explore the surge of religious spiritualism promoted by Jamaah Maiyah Cak Nun using a qualitative research framework. In addition, this research leads to a social and religious anthropological research model that combines virtual ethnography and fieldwork. The results of this study revealed the existence of spiritualism promoted by Jamaah Maiyah Cak Nun. Meanwhile, the development of various models of different aspects of spiritualism could not be separated from the support of the community itself. The Jamaah Maiyah's interaction also deserved attention; universal religious expressions and egalitarianism were the domains of the community. This research should be a reference for developing religious and social discourse in the future.